An updated comprehensive review of advances on structural features, catalytic mechanisms, modification methods and applications of chitosanases. (July 2022) - Xu, Yinxiao; Li, Li; Cao, Shengsheng; Zhu, Benwei; Yao, Zhong
Abstract: Chitosan is a kind of linear alkaline polysaccharide, which consists of N -acetyl-D -glucosamine units and D -glucosamine units. Both chitosan and its degradation products (chitosan oligosaccharides) possess versatile biological activities such as antitumor, antioxidant, antimicrobial, and anti-inflammatory activities. Therefore, chitosan and its chitosan oligosaccharides held great potential in food, medicine, agriculture and other fields. Chitosanases are a class of glycoside hydrolases that could specifically degrade deacetylated chitosan and they could break the β-1, 4-glycosidic bonds between glucosamines. Chitosanases have been widely used in various fields, such as preparation of chitosan oligosaccharides (COS) with unique physiological activities, as biocontrol agents for plant pest and disease resistance, to facilitate chitosan-mediated gene delivery and to prepare protoplasts. Therefore, researches on the fundamentals and applications of chitosanases have received extensive and increasing attention. It is very important to summarize and discuss the results of the previous studies to carry out the subsequent work. In this review, we discuss the research progress on the structures, catalytic mechanisms, molecular modifications and applications of the chitosanases. This comprehensive information should be helpful to expand the applications of chitosanases. Data availability: No data was used for the research described in the article. Data will be made available on request. Highlights: The structural features of chitosanases have been systematically discussed. The catalytic mechanism of different types of chitosanases has been elucidated. The enzymatic preparation of chitosan oligosaccharides has been summarized.